White matter abnormalities in Gulf War veterans with posttraumatic stress disorder: A pilot study. (January 2015) - Bierer, Linda M.; Ivanov, Iliyan; Carpenter, David M.; Wong, Edmund W.; Golier, Julia A.; Tang, Cheuk Y.; Yehuda, Rachel
Highlights: Gulf War veterans with and without PTSD were studied using diffusion tensor imaging. Cingulum bundles, connecting amygdala and medial frontal cortices, were of interest. Results showed lower mean diffusivity in the right cingulum bundle in PTSD. This suggests enhanced connectivity between amygdala and anterior cingulate cortex. Chronic multisymptom illness (CMI) alone did not affect DTI variables. Lower right cingulum mean diffusivity was only significant in the absence of CMI. Increased structural integrity in right cingulum was associated with PTSD severity. Increased structural integrity was also associated with higher cortisol responsivity. Summary: Background: Gulf War veterans were exposed to environmental toxins not present in other combat theaters resulting in a unique biological signature that only partially resembles that seen in other combat veterans with PTSD. Thus it is important to determine if brain abnormalities seen in non-Gulf War veterans with PTSD are also present in Gulf War veterans. In this pilot study, diffusion tensor imaging (DTI) tractography was used to assess the ultra-structural integrity of fronto-limbic white matter connections in Gulf War veterans with and without PTSD. The effects of chronic multisymptom illness on DTI measures was also evaluated. Methods: Subjects were 20 previously studied Gulf War veterans on whom MRIs had been obtained. Mean diffusivity (MD) and fractional anisotropy (FA) were determined for left and right cingulum bundle by DTI tractography and compared in separate analyses for 12 veterans with, and 8 without PTSD. The effect of chronic multisymptom illness and it's interaction with PTSD, were similarly investigated using multivariate ACOVA. Partial correlations were used to test the associations of both DTI indices with PTSD severity and plasma cortisol, controlling for whole brain volume. Results: Significantly lower MD was demonstrated in the right cingulum bundle among Gulf War veterans with PTSD. There were no significant differences in MD or FA in the left cingulum bundle. The presence of chronic multisymptom illness significantly attenuated the PTSD associated decrement in right cingulum MD. Clinician and self-rated PTSD symptom severity scores were significantly associated with reduced MD and increased FA in the right cingulum. Similar associations were observed for 8am plasma cortisol in a subset of participants. Conclusions: The preliminary findings indicate increased structural integrity – supporting enhanced connectivity – between right amygdala and anterior cingulate cortex in PTSD. This effect was strongest among Gulf War veterans without chronic multisymptom illness. The association of both MD and FA in the right cingulum with PTSD severity, and with heightened glucocorticoid responsivity, suggests that these DTI findings are a reflection of current PTSD illness expression. Although based on a small sample, these microstructural observations are consistent with a functional model suggesting increased amygdala responsivity in association with anterior cingulate modulation in PTSD.